B.0 = (x – 3)(x – 3)
C.0 = 2.4(x – 2)(x + 2)
D.0 = (x – 2)(x – 1)
Answer:
The decrease is exponential.
Step-by-step explanation:
An exponential decrease is something like:
f(x) = A*(r)^x with 0 < r < 1
A linear decrease is something like:
g(x) = -a*x + b with a > 0
First ai general formula.
If you have a quantity Q, decreased by an X%, the new quantity will be:
New Quantity = Q - Q*(X%/100%)
Now let's look at the question:
Suppose that the original price of the computer component is K
And the price as a function of the year is P(y)
Then we know that, in the year zero, the price is K.
P(0) = K
One year after, the price decreases by 2.25%
Then:
P(1) = K - K*(2.25%/100%) = K*(1 - 0.0225)
After another year, we will have another decrease of 2.25%
Then:
P(2) = K*(1 - 0.0225) - K*(1 - 0.0225)*(2.25%/100%)
P(2) = K*(1 - 0.0225)*(1 - 0.0225) = K*(1 - 0.0225)^2
We already can see the pattern, we can expect that in the year y, the price of the component will be:
P(y) = K*(1 - 0.0225)^y
This clearly is an exponential decrease.
what is the measure of angle B ?
Answer:
Step-by-step explanation:
Notice that buy construction of a parallelogram,the angles and must equal each other. Then, based on the info given, we can write the following equation:
Then, angle = which is also equal to angle B
and since the addition of all internal angles of the parallelogram must equal , then:
and therefore, since and must be equal, then:
(3.8) and (7,5)
Answer: A base of − cannot be used to rewrite because (−)
= −. A base of − can be used to rewrite because
(−)
= . If the exponent, , is even, (−)
will be positive. If the exponent, , is odd, (−)
cannot be a
positive number.
Step-by-step explanation: